Integração de conteúdo: técnica para solucionar problemas de conhecimento em conceitos computacionais adquirido pelo aprendiz - Coelho, Ubirajara Martin (2021)
The technique of Content Integration for the development of this thesis arose from the observations of the contents taught, from the activities developed in the classes of courses in the area of computer science and mainly from the difficulties of understanding and applying computational concepts, seeking to improve for the academic the learning of computational concepts. The general objective is to solve knowledge problems in computational concepts (e.g. the development of a wrong computational activity) acquired by the learner in the learning environment from an approach based on content integration, and to contribute to the teaching-learning process to improve student learning in computational concepts.. For this purpose, firstly, an apprenticeship knowledge check is carried out using Bloom's taxonomy to find out what level of knowledge the apprentice is at. With the inclusion of this technique, it is important to highlight that the learning of computational concepts can be thought of at the level of integration of partial, specific knowledge, with a view to general knowledge. It is considered that the content integration technique can be introduced in the context of learning as a way to unleash a better degree of knowledge of the academic. Four questions are motivating to be investigated: Does the learning environment favor the integration of content?; Do OC2-RD2 narratives introduced in the learning environment increase the effects of content integration (intradisciplinary and interdisciplinary)?; How do you know if the learner has managed to integrate content (intradisciplinary)?; Can the learner achieve the integration of content in integrative (interdisciplinary) activities ?. As answers to the investigated questions, we proposed a case study with the application of questions that address computational concepts studied in the classroom, with the aim of verifying the assimilation of computational concepts by the learners. For the verification of knowledge acquisition, the questions elaborated with computational concepts were used Bloom's Taxonomy as an instrument to verify the learner's knowledge. Subsequently the verification of knowledge acquisition, the integration of contents is worked on integrating activities through the laboratories of the disciplines, TCC, ENADE. As hypotheses of this research, they were postulated: the apprentices have acquired sufficient knowledge in the disciplines that is capable of accomplishing the integration of contents (intradisciplinary and interdisciplinary); the teacher has an affinity with the learning environment and teaching methodologies; the construction of narrative scenes OC2-RD2 brings a differential in the formation of computational concepts of the subjects addressed by the teacher in the learning environment from the use of the content integration technique. However, the integration of intradisciplinary and interdisciplinary content allows the learner to expand knowledge and learning, stimulating through teaching activities to make decisions, create challenges, plan actions, reflect and how to act to solve problems